THE EFFECT OF CORPORATE GOVERNANCE MECHANISMS AND AUDIT TENURE ON THE INTEGRITY OF FINANCIAL REPORTS IN FOOD AND BEVERAGE COMPANIES - Ni Putu Lisa Ernawatiningsih; I Dewa Made Endiana; Ni Putu Aprilia Dewayanti Putri Murtika (KRISNA: Kumpulan Riset Akuntansi, 2025)
The integrity of financial reports is defined as the extent to which the financial reports presented show correct and honest information. Financial reports can be said to have integrity if the financial reports presented are in accordance with the facts, there are no material errors that could influence the decisions of users of financial statements. This research aims to obtain empirical evidence regarding the influence of institutional ownership, managerial ownership, audit committee and audit tenure on integrity. financial reports on food and beverage companies listed on the Indonesia Stock Exchange for 2021-2023. The population of this research is food and beverage companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The number of companies used in this research was 27 companies which were determined using the purposive sampling method with 3 years of observation and obtained a total sample of 81 samples. The analysis technique used is multiple linear regression. The research results show that institutional ownership and managerial ownership have a positive effect on the integrity of financial reports. Meanwhile, independent commissioners, audit committees and audit tenure have no effect on the integrity of financial reports.